Kierkegaard and Indirect Communication: Theorizing HRD, Organizational Socialization, and Edification. (September 2013) - Herrmann, Andrew F.
Scholars have largely overlooked philosopher Soren Kierkegaard's thoughts on occupational, vocational, and work topics, although he did concern himself with occupational topics. This theoretical piece explores Kierkegaard's concept of "leveling" ( Nivelleringen ), connecting it to human resource development (HRD) and organizational socialization processes, which are often conducted by HRD departments. Organizational socialization is important as it provides newcomers with functional and cultural information. Similar to the concept of leveling, however, organizational socialization can provide employees with taken-for-granted socially constructed definitions of the self. This article proposes expanding edification and capability for individuals in the workplace via Kierkegaardian indirect communication in HRD and organizational socialization practices.